ANALISIS NILAI PENDIDIKAN DALAM NOVEL CAHAYA DI ATAS CAHAYA KARYA OKI SETIANA DEWI - Rohana Rohana (LPPM STKIP PGRI Bandar Lampung, 2020)
The problems raised in this study are related to the analysis of educational values ​​in the novel Cahaya di Atas Cahaya by Oki Setiana Dewi. The educational aspects studied include aesthetic (beauty), moral, religious and social aspects. The purpose of this research is to describe the value of education in the novel Cahaya di Atas Cahaya by Oki Setiana Dewi and to find out the dominant value and its relevance in the reader's life. This research uses descriptive qualitative method. The results of data analysis that have been carried out on the novel Cahaya di Atas Cahaya by Oki Setiana Dewi which is studied from its educational values, both aesthetics (beauty), moral, religious and social, strongly indicate the existence of educational values ​​that are beneficial to readers and connoisseurs of literature in particular. novelist. The value of education in the aesthetic education aspect tells about the beauties of real work as reality based on God's truth. The value of education, especially moral education, such as being devoted to parents, positive thinking in all things faced, not being arrogant and selfish, and always being able to care for others and not being arrogant towards something you have and being able to control yourself in any situation. Educational values ​​in the aspect of social education include always thinking positively towards others, needing each other, knowing hostility, having courtesy, always forgiving others mistakes, and being able to understand differences in beliefs. The value of religious education is such as the attitude of always being patient in dealing with endless problems, having good morals and ethics.